Competitive Adsorption of Cu2+, Pb2+ and Ni2+ on Thiourea Modified Spent Grated Coconut (Cocos Nucifera) - N. Dilah, N.; A.K.M. Hanafiah, M.; Khalid, K.; C. Ibrahim, S.; S. Hamzah, A. (International Journal of Engineering and Technology, 2018)
The behavior of thiourea spent grated Cocos nucifera (TSGC) as an adsorbent for simultaneous removal of Cu2+, Pb2+ and Ni2+ ions from aqueous solutions in ternary system was investigated. TSGC was characterized by using a CHNOS analyser, a Fourier transform infrared (FTIR) spectrometer and a scanning electron microscope coupled with energy dispersive spectrometer (SEM-EDS). Complexation was one of the main mechanisms involved as indicated by the FTIR spectra. The pseudo-second-order and Langmuir isotherm models best fit to the adsorption experimental data. The maximum adsorption capacities (mmol.g-1) of heavy metal ions by TSGC were in the order of Cu2+ (1.38) > Pb2+ (0.32) > Ni2+ (0.24). Overall, TSGC showed a higher selectivity for the Cu2+ ion.Â Â